Synthesis of an Ag@AgCl catalyst with amorphous copper as the support and its catalytic performance in the reduction of 4-nitrophenol. Issue 5 (May 2021) - Zhang, Jian; Qin, Chenchen; Liu, Luying; Dong, Hanfeng; Wang, Yujuan; Bao, Lei; Gan, Wei; Fu, Xucheng; Hao, Hequn
The support used in a composite catalyst has an important influence on the catalytic performance of the catalyst. Amorphous metals have good electron-transfer properties and the presence of defect structures on the surface will introduce additional active sites and should be excellent catalyst supports. In this study, an Ag@AgCl composite catalyst with amorphous Cu (a-Cu) as the support is prepared by a two-step precipitation method at room temperature and a light irradiation reduction method. Compared to the Ag@AgCl and a-Cu, the catalytic rate of the Ag@AgCl/a-Cu composite catalytic rate was 2.04 times and 6.69 times faster during the reduction of 4-NP in NaBH4 aqueous solution. The high-performance catalytic efficiency and reusability of Ag@AgCl/a-Cu may be attributed to the synergistic effect between Ag@AgC and amorphous metal elements. This work may provide an effective reference for the synthesis of high activity catalysts using amorphous metals as supports.